Practical Threshold RSA Signatures Without a Trusted Dealer - Damgård, Ivan B.; Koprowski, Maciej (BRICS Report Series, 2000)
We propose a threshold RSA scheme which is as efficient as the fastest previous threshold RSA scheme (by Shoup), but where two assumptions needed in Shoup’s and in previous schemes can be dropped, namely that the modulus must be a product of safe primes and that a trusted dealer generates the keys.